Students' Perceptions of Integrating Qalam AI and Teacher Competencies in Arabic Reading Instruction - Restu Budiansyah Rizki; Muhammad Fatkhur Rizal; Chusnia Rahmawati (LISANIA: Journal of Arabic Education and Literature, 2024)
In the educational context, the advancement of artificial intelligence technology, such as Qalam AI, brought significant positive impacts due to its ability to analyze morphological (sharf) and syntactic (nahw) patterns within Arabic sentences. However, this potential must be complemented by teachers' competencies in validating the results of Qalam AI's analysis of Arabic texts. This study explored students' perceptions of integrating Qalam AI and teacher competencies in Arabic reading instruction. This study used a quantitative approach. The sampling technique used in this study was a convenience sampling method with 150 participants selected from various educational institutions. The data collection technique involved questionnaires. The effectiveness questionnaire assessed five key indicators: ease of learning, material comprehension, student satisfaction, interest and motivation, and learning activity. The validity test of this research used Pearson product-moment, and the reliability test used Cronbach's alpha formula. The questionnaire was tested for validity and reliability using SPSS 24. The validity and reliability tests of the instrument showed that each statement was valid and reliable. The research results indicated students "agree" that integrating Qalam AI and teacher competencies could facilitate understanding of the material and enhance learning activities. Additionally, it showed students "strongly agree" that this integration could simplify learning, provide satisfaction, and increase student interest and motivation. Therefore, it could be concluded that integrating Qalam AI technology and teacher competencies could be utilized in the educational context, particularly in the teaching and learning processes such as reading instruction.